Recurrent microdeletions of 15q25.2 are associated with increased risk of congenital diaphragmatic hernia, cognitive deficits, and possibly Diamond-Blackfan anemia - Wat, Margaret J. (2010)
BACKGROUND: Congenital diaphragmatic hernia (CDH) can occur in isolation or in association with other abnormalities. We hypothesized that some cases of non-isolated CDH are caused by novel genomic disorders. METHODS AND RESULTS: In a cohort of >12,000 patients referred for array comparative genomic hybridization testing, we identified three individuals—two of whom had CDH—with deletions involving a ~2.3 Mb region on chromosome 15q25.2. Two additional patients with deletions of this region have been reported, including a fetus with CDH. Clinical data from these patients suggest that recurrent deletions of 15q25.2 are associated with an increased risk of developing CDH, cognitive deficits, cryptorchidism, short stature, and possibly Diamond-Blackfan anemia (DBA). Although no known CDH-associated genes are located on 15q25.2, four genes in this region—CPEB1, AP3B2, HOMER2 and HDGFRP3—have been implicated in CNS development/function and may contribute to the cognitive deficits seen in deletion patients. Deletions of RPS17 may also predispose individuals with 15q25.2 deletions to DBA and associated anomalies. CONCLUSIONS: Individuals with recurrent deletions of 15q25.2 are at increased risk for CDH and other birth defects. A high index of suspicion should exist for the development of cognitive defects, anemia, and DBA-associated malignancies in these individuals.